2012
DOI: 10.1242/jcs.099267
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear import of hTERT requires a bipartite nuclear localization signal mediated by Akt phosphorylation

Abstract: SummarySustained cell proliferation requires telomerase to maintain functional telomeres that are essential for chromosome integrity and protection. Although nuclear import of telomerase transcriptase (hTERT) is required for telomerase activity to elongate telomeres in vivo, the molecular mechanism regulating nuclear localization of hTERT is unclear. We have identified a bipartite nuclear localization signal (NLS; amino acid residues 222-240) that is responsible for nuclear import of hTERT. Immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 60 publications
6
81
1
1
Order By: Relevance
“…We have previously identified a bipartite NLS (222-RRRGGSASRSLPLPKRPRR-240) that is responsible for the nuclear import of hTERT (Chung et al, 2012). Mutations in the two clusters of basic amino acids in the bipartite NLS results in reduced nuclear localization of hTERT.…”
Section: A Bipartite Nls Is Essential For Nuclear Import Of Htertmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously identified a bipartite NLS (222-RRRGGSASRSLPLPKRPRR-240) that is responsible for the nuclear import of hTERT (Chung et al, 2012). Mutations in the two clusters of basic amino acids in the bipartite NLS results in reduced nuclear localization of hTERT.…”
Section: A Bipartite Nls Is Essential For Nuclear Import Of Htertmentioning
confidence: 99%
“…Mutations in the two clusters of basic amino acids in the bipartite NLS results in reduced nuclear localization of hTERT. We have also shown that Akt-mediated phosphorylation at S227 is necessary for efficient nuclear translocation of hTERT (Chung et al, 2012). To determine whether nuclear localization of hTERT is affected by different cellular backgrounds, several cell lines -including MCF7, H1299 and U2OS cells -were transfected with Flag-hTERT and various mutant constructs (Flag-7A, Flag-S227A and Flag-S227E, see Fig.…”
Section: A Bipartite Nls Is Essential For Nuclear Import Of Htertmentioning
confidence: 99%
See 2 more Smart Citations
“…(110) TERT is imported from the cytoplasm to the nucleus through Akt-mediated phosphorylation at serine 227 and its interaction with heath shock protein 90 (Hsp90). TERT localization is also regulated by interaction with other proteins such as nuclear factor kappa B (NF-kB) and tumor necrosis factor a (TNF-a) (111). TERT has a mitochondrial targeting signal and, therefore, TERT can enter the mitochondrial matrix where it interacts with mitochondrial DNA and mitochondrial tRNA (112).…”
Section: Dna Damage and Nddmentioning
confidence: 99%